1999
DOI: 10.1046/j.1440-1703.1999.141277.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of fern gametophytes to the growth of produced sporophytes on the basis of carbon gain

Abstract: Sporophytes appeared on most gametophytes of Thelypteris palustris (Salisb.) Schott that reached a certain size, which is interpreted to be a critical size of gametophytes for the production of sporophytes. After sporophytes were produced, attached gametophytes ceased dry weight growth, but the gametophytes which did not produce sporophytes grew successively. It was hypothesized that matter produced by gametophytes was being supplied to young sporophytes. Photosynthesis and respiration of gametophytes with att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…The growth patterns of cut and intact gametophytes were similar. The growth of SGs decreased during the ten days after sporophyte emergence; thereafter, growth ceased, as observed in a related study by Sakamaki and Ino (1999). Figures 2b-2d show the growth of sporophytes produced on CGs and IGs.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…The growth patterns of cut and intact gametophytes were similar. The growth of SGs decreased during the ten days after sporophyte emergence; thereafter, growth ceased, as observed in a related study by Sakamaki and Ino (1999). Figures 2b-2d show the growth of sporophytes produced on CGs and IGs.…”
Section: Resultssupporting
confidence: 75%
“…They noted that sporophyte development would affect the formation of successive sporophytes and affect decay of the gametophytes by the inhibitor. In our previous study (Sakamaki and Ino 1999) we demonstrated that in the first 10 days after emergence of a sporophyte, gametophyte organic matter production was sufficient to produce two or more sporophytes. In addition, two or three sporophytes of similar size can, rarely, grow on a single gametophyte.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…According to Sakamaki & Ino (1999), gametophytes allocated photosynthate for sporophyte growth and it was an important aid before the one-leaf stage. They concluded that the higher photosynthetic rates of gametophytes in the early stage were important for reaching the critical size for sporophyte production in a short time.…”
Section: Resultsmentioning
confidence: 99%